Research Competencies to Develop Academic Reading and Writing: A Systematic Literature Review - Castillo-Martínez, Isolda Margarita; Ramírez-Montoya, María Soledad (Frontiers in Education, 2021)
Rationale: The development of research skills in the higher education environment is a necessity because universities must be concerned about training professionals who use the methods of science to transform reality. Furthermore, within research competencies, consideration must be given to those that allow for the development of academic reading and writing in university students since this is a field that requires considerable attention from the educational field at the higher level. Objective: This study aims to conduct a systematic review of the literature that allows the analysis of studies related to the topics of research competencies and the development of academic reading and writing. Method: The search was performed by considering the following quality criteria: (1) Is the context in which the research is conducted at higher education institutions? (2) Is the development of academic reading and writing considered? (3) Are innovation processes related to the development of academic reading and writing considered? The articles analyzed were published between 2015 and 2019. Results: Forty-two papers were considered for analysis after following the quality criterion questions. Finally, the topics addressed in the analysis were as follows: theoretical–conceptual trends in educational innovation studies, dominant trends and methodological tools, findings in research competencies for innovation in academic literacy development, types of innovations related to the development of academic reading and writing, recommendations for future studies on research competencies and for the processes of academic reading and writing and research challenges for the research competencies and academic reading and writing processes. Conclusion: It was possible to identify the absence of studies about research skills to develop academic literacy through innovative models that effectively integrate the analysis of these three elements.